Efficient methods for hierarchical multi-omic feature extraction and visualisation. (21st July 2020) - Becker, Timothy; Shin, Dong-Guk
A single DNA alignment file can be resource intensive to visualise at arbitrary scale given current visualisation systems. We address this limitation by integrating a parallel out-of-core feature extraction algorithm with a disk based hierarchical data store that is several orders of magnitude faster for visualisation tasks. To demonstrate the utility of our approach, we designed a high-performance web application that serves translated data to an interactive client. We incorporate novel visualisation of these data features, while allowing user-specified resolution and response. Unlike per-read techniques which can run out of memory when displaying large scale genomic variations, our data structure returns a controllable representation of that region, making the technique ideally suited for visualisation of multiple large data sets. We describe our open-source feature extraction framework and web-based visualization while comparing the performance to current systems.